2010
DOI: 10.4097/kjae.2010.59.s.s191
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative acute brain swelling when performing indirect anastomosis in a patient with moyamoya disease -A case report-

Abstract: A 6-year-old male patient who was suffering from a cold and a transient ischemic attack was scheduled to undergo encephalo-duro-arterio-synangiosis for treating his moyamoya disease. Acute brain edema occurred just after opening the dura mater. Head elevation, reduction of the head rotation and hyperventilation were done. The inhalational agents were discontinued and total intravenous anesthesia was started. The swelling was reduced after intravenously infusing mannitol. An abrupt return from hypocapnia to nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Unilateral direct bypass in symptomatic hemispheres of MMD patients could cause impairment of cerebrovascular regulation in primary asymptomatic hemispheres shortly after surgery, which may result in the occurrence of infarction and hemorrhage in the whole brain 62 , 63 . Even anesthesia can induce intraoperative, acute brain swellin 64 .…”
Section: Postoperative Infarction and Non-hs-induced Hemorrhagementioning
confidence: 99%
“…Unilateral direct bypass in symptomatic hemispheres of MMD patients could cause impairment of cerebrovascular regulation in primary asymptomatic hemispheres shortly after surgery, which may result in the occurrence of infarction and hemorrhage in the whole brain 62 , 63 . Even anesthesia can induce intraoperative, acute brain swellin 64 .…”
Section: Postoperative Infarction and Non-hs-induced Hemorrhagementioning
confidence: 99%
“…Similarly, these fragile cerebral blood vessels with impaired cerebrovascular regulation have tendency for postoperative infarction and hemorrhage involving the asymptomatic cerebral hemisphere as well 6 . One previous study 7 has also reported acute brain swelling intraoperatively due to anesthesia.…”
Section: Technical Notementioning
confidence: 91%